Anticholinergic medication use in elderly people living with HIV and self-reported neurocognitive impairment: a prospective cohort study. (3rd November 2021) - Jakeman, Bernadette; Scherrer, Alexandra; Battegay, Manuel; Gunthard, Huldrych F.; Hachfeld, Anna; Calmy, Alexandra; Schmid, Patrick; Bernasconi, Enos; Cavassini, Matthias; Marzolini, Catia
Abstract: Background: Anticholinergic (ACH) medications have been associated with neurocognitive impairment, particularly in the elderly. This study determined prospectively the prevalence of prescribed ACH medications and their association with self-reported neurocognitive impairment (SRNI) in elderly people living with HIV (PLWH) of the Swiss HIV Cohort Study (SHCS). Methods: A literature review was performed to identify ACH medications, which were scored 0 to 3 (higher score indicating more ACH burden). Prescriptions were reviewed in July 2019 for all SHCS participants ≥65 years old to assess the prevalence of ACH medications. Association between ACH burden and neurocognitive impairment was evaluated using the SHCS SRNI questions addressing memory loss, attention difficulties and slowing in reasoning. Results: One thousand and nineteen PLWH (82% male) with a median age of 70 (IQR = 67–74) years were included. Most participants were on ART (99%). The average number of non-HIV drugs was 5.1 ± 3.6, representing a polypharmacy prevalence of 50%. Two hundred participants (20%) were on ≥1 ACH medication, with an average ACH score of 1.7 ± 1.3. SRNI, adjusted for age, sex, CD4, nadir CD4, viral load, efavirenz use and polypharmacy, was associated with depression (OR = 4.60; 95% CI = 2.62–8.09) and a trend was observed with being on ≥1 ACH medication (OR = 1.69; 95% CI = 0.97–2.95). In a subgroup analysis of participants without depression ( n = 911), SRNI was associated with the use of ≥1 ACH medication (OR = 2.51; 95% CI = 1.31–4.80). Conclusions: ACH medication use is common in elderly PLWH and contributes to SRNI. The effect of ACH medications on neurocognitive impairment warrants further evaluation using neurocognitive tests.